Capsule Protects Acinetobacter baumannii From Inter-Bacterial Competition Mediated by CdiA Toxin - Krasauskas, Renatas; Skerniškytė, Jūratė; Martinkus, Julius; Armalytė, Julija; Sužiedėlienė, Edita (Frontiers in Microbiology, 2020)
Currently, Acinetobacter baumannii is considered as one of the most important infectious agents causing hospital acquired infections worldwide. It has been observed that many clinically important pathogens express contact-dependent growth inhibition (CDI) phenomenon, which modulates cell-cell and cell-environment interactions, potentially allowing bacteria to adapt to ever-changing conditions. Mainly, these systems are used for the inhibition of the growth of genetically different individuals within the same species. In this work, by performing cell competition assays with three genotypically different (as determined by pulse-field gel electrophoresis) clinical A. baumannii isolates II-c, II-a, and II-a1, we show that A. baumannii capsule is the main feature protecting from CDI-mediated inhibition. We also observed that for one clinical isolate, the two-component BfmRS system, contributed to the resistance against CDI-mediated inhibition. Moreover, we were able to demonstrate, that the effector protein CdiA is released into the growth media and exhibits its inhibitory activity without the requirement of a cell-cell contact. Lastly, by evaluating the remaining number of the cells pre-mixed with the CdiA and performing live/dead assay, we demonstrate that purified CdiA protein causes a rapid growth arrest. Our results indicate, that capsule efficiently protects A. baumannii from a CDI-mediated inhibition by a clinical A. baumannii V15 strain, which is able to secrete CdiA effector into the growth media and cause target cell growth arrest without cell-cell contact.